Insect Pest Management on Golf Courses - Eileen A. Buss (EDIS)
Revised! ENY-351, a 14-page illustrated fact sheet by Eileen A. Buss, describes the biology and management of the most important insect pests on golf courses in Florida. Published by the UF Department of Entomology and Nematology, June 2009.